Socioemotional Resources Account for Academic Adjustment in Moroccan Adolescents - Cortés-Denia, Daniel; El Ghoudani, Karima; Pulido-Martos, Manuel; Alaoui, Smail; Luque-Reca, Octavio; Ramos-Álvarez, Manuel Miguel; Augusto-Landa, José María; Zarhbouch, Benaissa; Lopez-Zafra, Esther (Frontiers in Psychology, 2020)
This study aimed to analyze the relationship of both positive socioemotional resources (emotional intelligence and social support) and negative states (test anxiety and depression) with academic adjustment, as measured by academic performance and self-concept, among Moroccan adolescents. The participants were 845 students from Morocco (372 boys, 473 girls; mean age 15.58 years; SD = 1.69; range = 13 to 18) who were attending secondary education (79.8%) or high school. The participants completed a questionnaire that included scales to measure the variables of interest, adapted for and validated in Moroccan adolescents. A multiple mediation serial model with four mediator variables confirmed that academic self-concept was positively and directly predicted by emotional intelligence, academic performance and social support, whereas test anxiety and depression had a negative effect. Second, emotional intelligence predicted self-concept through its indirect effects on test anxiety and academic performance, social support, and depression. Emotional intelligence was the most protective factor. This model has good performance in explaining the variation in test anxiety (1.6%), depression (14.2%), social support (9.5%), academic performance (6.8%) and self-concept (35.7%). This study helps clarify the relationship of positive and negative socioemotional states with the academic performance of adolescents in Morocco. This study contributes to the literature by enhancing knowledge of adolescents in societies that, like Morocco, have a less elaborated tradition at these levels of education and that are considering education in their agenda as a way of enhancing national development and promoting emotional intelligence to allow youth development in a healthier society.